Performance of steel slag for wearing course compared with conventional wearing course - Shokri, Manouchehr (2014)
Transportation and highway orientation are going to use from sustainable material and recycling material. As the amount of disposed industrial waste material is increasing in road construction, researchers are exploring the use of waste materials which could preserve natural resources and save the environment. One of these sustainable materials is Steel-furnace slag, which is a synthetic aggregate produced as a consequence of the electric arc furnace (EAF). Steel slag was select due to its characteristics, which are almost similar to conventional aggregates, and the fact that it is easily obtainable as a by-product from the steel industry. The same gradations of mixtures would produce using normal crushed aggregate as control samples. This project was carried out to evaluate the performance of EAF steel slag aggregate in AC 14-wearing course mix, where the conventional granite aggregate was replaced with steel slag. In addition the following mix design and performance characterization of the bituminous and aggregates (steel slag aggregates and conventional aggregates) were evaluated in this project through creep tests, Resilient modulus tests at various temperatures, texture depth, skid resistance. The bitumen 60-70 PEN was used and percentage of Steel Slag was considered 0, 30, 50 and 100% for each sample. All the mixtures with EAF Steel slag have satisfied the requisites for acceptance in the road sector technical standards, thus resulting as suitable for use in the construction of road infrastructures. Samples made from steel slag showed considerably better results than conventional aggregate. Therefore, operation of steel slag would reduce land fill, save natural resources and improve the strength of pavement to sustain a higher volume of vehicles. on the other hand, laboratory test result results illustrates better performance against deformation characteristics, skid resistance, stripping of the binder and lateral movement of material compare with conventional wearing course.